The Role of the Body Mass Index in the Acute Pancreatitis Evolution - PADUREANU, VLAD (Curr Health Sci J, 2021)
The etiological factors involved in acute pancreatitis are multiple, both pancreatic and extra-pancreatic, having a predisposing or triggering role. The purpose of our study was to evaluate the role of BMI (body mass index) in the evolution of acute pancreatitis. The study was performed between January 2018-October 2020 on a lot of 110 patients diagnosed with acute pancreatitis and admitted to the 1(st)Surgery Clinic and the 2(nd)Medical Clinic of the Craiova Emergency County Clinical Hospital, the study was prospective. The control lot consisted of patients who were not diagnosed with acute pancreatitis (n=232).Comparing the distributions according to the body mass index of the two groups by the Chi square test, a statistically significant difference is observed (p<0.05) regarding the obese patients who are diagnosed with acute pancreatitis. Obesity patients have an increased risk of developing acute pancreatitis compared to non-obese patients.